Effect of Heat Treatment on Microstructure of Zinc Aluminum Hybrid Composite Cast Alloys - Serdar Aslan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The matrix material ZA27 alloy was used in the production of metal matrix composite material. SiC and graphite were used as reinforcement materials in the study. ZA27 alloy with 10% SiC, 2.5% , 5% , 7.5% and 10% graphite and 10% SiC + 2.5% , 5%, 7.5%, 10% graphite reinforcement by weight hybrid composite material was produced. The microstructures were examined by SEM and EDS and the results were discussed. In the investigations, SiC and graphites had a heterogeneous nucleating effect during the solidification of the alloy. In addition, thin dendrites showed a tendency to become spherical by heat treatment.